Risk factors affecting health of modern specialists in vocational and psychological training - Tverdokhliebova, Natalia; Yevtushenko, N. S. (Харківський національний педагогічний університет ім. Г. С. Сковороди, 2023)
The health of people in Ukraine has become particularly relevant in recent years, as Ukrainian society is exposed to unprecedented external threats, such as the war with Russia, that negatively affect plans, goals and quality of life, and the increases psychological tensions that lead to the deterioration of people's physical, mental and social health. This also applies eqully to participants in the educational environment. Today, in light of the military actions in Ukraine, it is necessary in higher educational institutions to address new and non-standard tasks challenge students’ health and their personal resources in the process of education. A complex combination of new and unpredictable challenges and risks resulting from challenges to the socio-political situation in the country such as the Covid pandemic, the war with Russia, and the growing presence of digital technologies in the educational space, actualizes the deployment of a series of studies about risk factors affecting students’ health.

У межах нашого дослідження було досягнуто наступних результатів: узагальнено погляди науковців до визначення факторів, що впливають на рівень здоров’я молоді; розглянуто фактори ризику, що впливають на показники здоров’я студентів; надано результати дослідження поширеності захворювань у студентів спеціальної медичної групи Національного технічного університету «Харківський політехнічний інститут», сформульовано рекомендації щодо профілактики захворюваності серед студентів вищих навчальних закладів у процесі професійної підготовки в умовах війни.
Дослідження факторів ризику, що впливають на здоров'я у процесі професійно-психологічної підготовки сучасного фахівця
Keywords: students’ health; healthy lifestyle; risk factors; specialists’ training; preventive measures; disease prevention; здоров'я студентів; здоровий спосіб життя; фактори ризику; підготовка фахівців; профілактичні заходи; попередження захворюваності